Genome-wide analysis of R2R3-MYB genes in cultivated peanut (Arachis hypogaea L.): Gene duplications, functional conservation, and diversification - Wang, Sijian; Xu, Zhe; Yang, Yiwen; Ren, Weifang; Fang, Jiahai; Wan, Liyun (Frontiers in Plant Science, 2023)
The cultivated Peanut (Arachis hypogaea L.), an important oilseed and edible legume, are widely grown worldwide. The R2R3-MYB transcription factor, one of the largest gene families in plants, is involved in various plant developmental processes and responds to multiple stresses. In this study we identified 196 typical R2R3-MYB genes in the genome of cultivated peanut. Comparative phylogenetic analysis with Arabidopsis divided them into 48 subgroups. The motif composition and gene structure independently supported the subgroup delineation. Collinearity analysis indicated polyploidization, tandem, and segmental duplication were the main driver of the R2R3-MYB gene amplification in peanut. Homologous gene pairs between the two subgroups showed tissue specific biased expression. In addition, a total of 90 R2R3-MYB genes showed significant differential expression levels in response to waterlogging stress. Furthermore, we identified an SNP located in the third exon region of AdMYB03-18 (AhMYB033) by association analysis, and the three haplotypes of the SNP were significantly correlated with total branch number (TBN), pod length (PL) and root-shoot ratio (RS ratio), respectively, revealing the potential function of AdMYB03-18 (AhMYB033) in improving peanut yield. Together, these studies provide evidence for functional diversity in the R2R3-MYB genes and will contribute to understanding the function of R2R3-MYB genes in peanut.